Safety and immunogenicity of an AMA1 malaria vaccine in Malian children: results of a phase 1 randomized controlled trial. - Mahamadou A Thera; Ogobara K Doumbo; Drissa Coulibaly; Matthew B Laurens; Abdoulaye K Kone; Ando B Guindo; Karim Traore; Mady Sissoko; Dapa A Diallo; Issa Diarra; Bourema Kouriba; Modibo Daou; et al. (PLoS ONE)
Background The objective was to evaluate the safety and immunogenicity of the AMA1-based malaria vaccine FMP2.1/AS02(A) in children exposed to seasonal falciparum malaria. Methodology/principal findings A Phase 1 double blind randomized controlled dose escalation trial was conducted in Bandiagara, Mali, West Africa, a rural town with intense seasonal transmission of Plasmodium falciparum malaria. The malaria vaccine FMP2.1/AS02(A) is a recombinant protein (FMP2.1) based on apical membrane antigen 1 (AMA1) from the 3D7 clone of P. falciparum, formulated in the Adjuvant System AS02(A). The comparator vaccine was a cell-culture rabies virus vaccine (RabAvert). One hundred healthy Malian children aged 1-6 years were recruited into 3 cohorts and randomized to receive either 10 microg FMP2.1 in 0.1 mL AS02(A), or 25 microg FMP2.1 in 0.25 mL AS02(A), or 50 microg FMP2.1 50 microg in 0.5 mL AS02(A), or rabies vaccine. Three doses of vaccine were given at 0, 1 and 2 months, and children were followed for 1 year. Solicited symptoms were assessed for 7 days and unsolicited symptoms for 30 days after each vaccination. Serious adverse events were assessed throughout the study. Transient local pain and swelling were common and more frequent in all malaria vaccine dosage groups than in the comparator group, but were acceptable to parents of participants. Levels of anti-AMA1 antibodies measured by ELISA increased significantly (at least 100-fold compared to baseline) in all 3 malaria vaccine groups, and remained high during the year of follow up. Conclusion/significance The FMP2.1/AS02(A) vaccine had a good safety profile, was well-tolerated, and induced high and sustained antibody levels in malaria-exposed children. This malaria vaccine is being evaluated in a Phase 2 efficacy trial in children at this site. Trial registration ClinicalTrials.gov NCT00358332 [NCT00358332].